Isolation and Characterization of Vermamoeba vermiformis from Swimming Pools in Lahore, Pakistan - Muhammad Tariq Zahid; Amber Chayyan; Asmat Ullah; Ayesha Razzaq; Romassa Sajid; Atiqa Ikhlaq; Khajid Ullah Khan; Ghulam Mustafa (BioScientific Review, 2024)
Background. Free-living amoebae (FLA) are common in aquatic environments and their interaction with humans can lead to significant public health risks. Many of these amoebae are opportunistic pathogens, causing infrequent yet severe diseases. Vermamoeba vermiformis, a widely distributed FLA, has been associated with keratitis infection, often in conjunction with Acanthamoeba. Furthermore, V. vermiformis can serve as a host for pathogenic bacteria, such as Legionella pneumophila and Stenotrophomonas maltophilia, amplifying potential health risks. This study aimed to investigate the presence of FLA in three (3) swimming pools situated in Lahore, Pakistan.Methodology. A total of eighteen (18) water samples were collected from the swimming pools and filtered using 0.45μm cellulose acetate filter papers. The filter papers were carefully placed upside down on non-nutrient agar (NNA) plates seeded with heat-attenuated E. coli. A pure culture of FLA was obtained through repeated subculturing on NNA plates seeded with E. coli, ensuring the results' reliability and validity.Results. Samples from all three (3) pools exhibited the presence of FLA. The isolated FLA was identified as V. vermiformis based on its morphological appearance under the light microscope, and molecular characterization was performed using the SSU rRNA gene sequence. The trophozoites of V. vermiformis were elongated and cylindrical, with a single pseudopodium, giving them a limax shape. The cysts of V. vermiformis had a double-walled oval and round structure. A clear hyaloplasm was observed at the anterior end of the pseudopodia of actively moving V. vermiformis under a light microscope.Conclusion. SSU rRNA, gene-based, molecular characterization confirmed isolated FLA as a local isolate of V. vermiformis. Phylogenetic analysis indicated its close homology with Echinamoeba. The presence of V. vermiformis in swimming pool water poses a potential threat to human health, as it is an opportunistic pathogen and a well-known host of different pathogenic bacteria.